2005
DOI: 10.1111/j.1467-9590.2005.00318.x
|View full text |Cite
|
Sign up to set email alerts
|

Rossby Waves on a Shear Flow with Recirculation Cores

Abstract: Large-amplitude Rossby waves riding on a background flow with a weak shear can be calculated up to a critical amplitude for which the meridional velocity, in a frame traveling with the wave, approaches zero at some point. Here we consider waves with an amplitude slightly greater than the critical amplitude by incorporating a region of recirculating fluid (vortex core) near this critical point. The effect of the vortex core is to introduce an extra nonlinear term into the equation for the wave amplitude proport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…The case when the trapped core and multiscaling are combined together is beyond the scope of the present study and will be presented elsewhere. It is noted that multiscaling phenomena exist for solitary waves in various physical contexts, for example, for Rossby waves on a shear flow (Derzho and Grimshaw, 2005) or inertial waves in swirling flows (Derzho and Grimshaw, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The case when the trapped core and multiscaling are combined together is beyond the scope of the present study and will be presented elsewhere. It is noted that multiscaling phenomena exist for solitary waves in various physical contexts, for example, for Rossby waves on a shear flow (Derzho and Grimshaw, 2005) or inertial waves in swirling flows (Derzho and Grimshaw, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Derzho and Grimshaw (2005) reported that solitary Rossby waves in channels obey the same KdV-type equation with complicated nonlinearity due to the mean shear variations. A Coriolis force for Rossby waves plays the same role as gravitational force for the internal gravity waves.…”
Section: Multiscalingmentioning
confidence: 99%
“…Following the pioneering work of Benney [2] and recent papers of Derzho and Grimshaw [10,11] and Clarke and Grimshaw [3], we discuss large amplitude Rossby waves riding on a background flow with a weak shear in a meridional channel bounded by rigid latitudinal boundaries at y = y 0 and y = y 0 + H . As |x| → ∞, the flow becomes a weakly mean shear flow given by…”
Section: Nonlinear Rossby Waves On a Weak Shear Flowmentioning
confidence: 99%
“…These studies are based on the assumption that there is no stagnation point or closed streamlines in the flow, that is, there is an implicit limitation on the amplitude of the waves. On the other hand, Derzho and Grimshaw [10] generalized Benney's work to the case of Rossby waves containing stagnation points in the interior.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation